1975
DOI: 10.1002/ijc.2910160512
|View full text |Cite
|
Sign up to set email alerts
|

Host responses within solid tumors: Non‐thymus‐derived specific cytotoxic cells within a murine mammary adenocarcinoma

Abstract: The nature of host-derived, specifically cytotoxic cells infiltrating solid murine mammary adenocarcinomas (line T1699) was investigated. Cell suspensions obtained from enzymatically dispersed tumors were separated by sedimentation velocity. The host cell fraction was heterogeneous and contained T-lymphocytes, non-phagocytic cells bearing Fc receptors, eosinophils and monocytes. Host cells equivalent in size to small lymphocytes and bearing Fc receptors were found to be the predominant cell type responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 24 publications
(13 reference statements)
3
25
0
Order By: Relevance
“…Similar data were obtained when infiltration by host cells of in-vivogrowing tumour was studied (Haskill et al, 1975). The role of these subpopulations of syngeneic lymphoid cells in MTS growth inhibition is at present being investigated in an in vitro assay.…”
supporting
confidence: 63%
“…Similar data were obtained when infiltration by host cells of in-vivogrowing tumour was studied (Haskill et al, 1975). The role of these subpopulations of syngeneic lymphoid cells in MTS growth inhibition is at present being investigated in an in vitro assay.…”
supporting
confidence: 63%
“…and has been adapt ed to tissue culture as previously described [14,30], A long-term culture line used in the present study produced progressively growing tumors in syngeneic hosts, when inoculated subcutaneously (s.c.) in the shoulder fat pad area, while similar tumors underwent spontane ous regression when the cells were inoculated s.c. in the belly. Origin and passage history of a fibrosarcoma SaD2 have been previously described 114).…”
Section: Tumor Cellsmentioning
confidence: 99%
“…In a syngeneic murine mammary adenocarcinoma T1699 growing in DBA/2J female mice, we have pre viously demonstrated that in situ effector cells [15,16) are specifically armed monocytes [14][15][16] and also that the serum from tumor-bearing hosts contained a non antibody factor(s) which could transfer specific anti tumor immunity to normal recipients. Such host immu nity provided by passive transfer of serum depended on some host cellular components [30].…”
Section: Introductionmentioning
confidence: 99%
“…HUMAN and transplantable animal tumours have been shown to contain a variety of host cells such as macrophages, lymphocytes and " null " cells, amongst the neoplastic cells (Birbeck and Carter, 1972; Eccles and Alexander, 1974; Evans, 1972;Gauci and Alexander, 1975;Haskill, Yamamura and Radov, 1975;Mansell et al, 1975;Russell, Doe and Cockrane, 1976;Szymaniec and James, 1976;van Loveren and den Wood, Gillespie and Barth, 1975). The reason for their presence, and the mechanism attracting them to the tumour, are not clear.…”
mentioning
confidence: 99%